Academic distress among undergraduate students during COVID-19: the relevance of SES and help-seeking behaviors - Korn, Liat; Zigdon, Avi; Davidovitch, Nitza (Frontiers in Psychology, 2023)
Introduction Academic distress has been frequently reported following the COVID-19 pandemic. This study estimates academic distress among undergraduate students, characterizes its nature in relation to economic, social, and health indicators, and examines the level of request for help following mental distress. Students with higher levels of academic distress were expected to show lower socio-economic status, lower social connections, and lower wellbeing indices. Methods A cross-sectional study based on a structured anonymous questionnaire was delivered online to more than 1,400 undergraduate students from one university in Israel (women, 66.7%). Results Academic distress was reported by 27.1% of the sample. Students who reported academic distress were more likely to report stress, negative psycho-somatic symptoms, changes in weight since COVID-19, low self-esteem, depressive symptoms, higher COVID-19 concerns, and higher security situation concerns. A hierarchic logistic regression model showed that the probability of reporting academic distress was 2.567 times higher (p < 0.001 95% CI [1.702, 3.871]) for those who reported lower family economic status before COVID-19 and 2.141 times higher (p = 0.004 95% CI [1.284, 3.572]) for those who highly reported depressive symptoms. In contrast, only 15.6% of those who reported academic distress sought help from academic authorities. Discussion The significant associations of academic distress with health indices indicate that the self-reported distress was real and highly related to adverse health measures. A comprehensive, collaborative model that integrates psychological, economic, and social aspects of intervention is required in times of crisis within academic institutions.